2001
DOI: 10.1016/s0022-4073(01)00024-3
|View full text |Cite
|
Sign up to set email alerts
|

Radiative properties of cirrus clouds in the infrared (8–) spectral region

Abstract: A ground-based observation system has been developed at the Meteorological Research Institute (MRI) for simultaneous measurements of cloud structure and radiative properties of high-level ice clouds. In this observation system, the cloud microphysical quantities and spectral radiances in the region of the 10um window could be simultaneously observed by a Hydrometeor Video Sonde (HYVIS) and a Fourier Transform Infrared (FTIR) spectro-radiometer. On the basis of the results measured by HYVIS, the size distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 76 publications
4
91
0
Order By: Relevance
“…Several parametrizations were developed for visible and infrared wavelengths (Magono, 1966;Labonnote et al, 2000;Yang et al, 2001Yang et al, , 2005Baum et al, 2005bBaum et al, , 2011Baran and Labonnote, 2007;Baran et al, 2009;Baran, 2012;Baran et al, 2013). For cirrus cases 1 to 8 we employ the aggregate ice crystal model (Yang et al, 2001(Yang et al, , 2005 with a monodisperse distribution used in the IIR retrieval algorithm (Garnier et al, 2013) that provides an extinction coefficient, a single-scattering albedo and an asymmetry factor (Yang et al, 2001(Yang et al, , 2005.…”
Section: Optical Property Parametrizationmentioning
confidence: 99%
“…Several parametrizations were developed for visible and infrared wavelengths (Magono, 1966;Labonnote et al, 2000;Yang et al, 2001Yang et al, , 2005Baum et al, 2005bBaum et al, , 2011Baran and Labonnote, 2007;Baran et al, 2009;Baran, 2012;Baran et al, 2013). For cirrus cases 1 to 8 we employ the aggregate ice crystal model (Yang et al, 2001(Yang et al, , 2005 with a monodisperse distribution used in the IIR retrieval algorithm (Garnier et al, 2013) that provides an extinction coefficient, a single-scattering albedo and an asymmetry factor (Yang et al, 2001(Yang et al, , 2005.…”
Section: Optical Property Parametrizationmentioning
confidence: 99%
“…[9] At present, ice crystal single scattering properties in the IR have been reliably calculated for hexagonal columns [Sun and Fu, 1999;Yang et al, 2001;Baran et al, 2001a] and planar polycrystals [Mitchell, 2002] using different theoretical approaches.…”
Section: Single Scattering Properties As Functions Of D Ementioning
confidence: 99%
“…[24] More recently, Yang et al [2001] have developed the stretched scattering potential method (SSPM) to overcome the discontinuity at size parameters around 20 between FDTD and IGOM results for the absorption coefficient in the IR, where strong absorption is involved. One possible reason for this discontinuity is the tunneling or above-edge effect, which indirectly has been taken into account in parameterizations involving Mie-Lorenz theory and in the approach of Sun and Fu [1999].…”
Section: Randomly Oriented Hexagonal Columnsmentioning
confidence: 99%
“…The RTM −1 (Zhou et al 2007(Zhou et al , 2009) used here only uses observed radiance and instrument random noise; no other 'truth' data from satellite or surface-based instruments or from numerical weather analysis/prediction models are utilized in assisting or constraining the retrieval products. The fast transmittance model used herein is a combination of the Stand-alone AIRS Radiative Transfer Algorithm (SARTA) Version 1.07 and the physically based cloud RTM based on the discrete ordinate radiative transfer (DISORT) calculations performed for a wide variety of cloud microphysical properties (Stamnes et al 1988, Yang et al 2001, Strow et al 2003. The studies presented here only deal with clear-sky conditions; therefore, DISORT (or the cloud radiative transfer) model error is not estimated.…”
Section: Analysis Demonstrationmentioning
confidence: 99%